Is breast-conserving therapy adequate in BRCA 1/2 mutation carriers? The radiation oncologist’s point of view - Vallard, Alexis (Br J Radiol, 2019)
Breast conserving therapy (BCT) is currently a recognized alternative to mastectomy for early BC patients. However, the therapeutic index of BCT was considered controversial for decades in BRCA1/2 mutation carriers. The aim of the present review was to investigate the outcome of mutation carriers undergoing BCT regarding local and distant endpoints. A short review was performed from the point of view of the radiation oncologist. Only retrospective data were available regarding local outcome assessment. They generated conflicting results. In studies with limited follow-up, BCT did not increase the risk of local recurrence in BRCA1/2 mutation carriers versus non-carriers. Conversely, some studies with longer follow-up supported that local relapse was increased in mutation carriers. Yet, according to some publications, their long-term risk of ipsilateral recurrence post-BCT was not different from general population cohorts. Besides, overall and metastasis-free survivals were the same after BCT regardless of the BRCA1/2 mutation status. Similar survival rates were also reported when BCT and mastectomy were compared in mutation carriers. Regarding acute or late toxicity, normal rates were reported in BRCA mutation carriers after breast radiotherapy. The BRCA1/2 mutation does not seem to widely alter the therapeutic index (efficacy/toxicity ratio) of modern adjuvant breast irradiation. Although the long term equivalence of BCT/mastectomy on local control is still not clearly recognised, BCT can be considered an adequate option for BRCA1/2 mutation carriers. This review highlights that BCT is a reasonable option for BRCA1/2 mutation carriers however litterature is controversial concerning long-term local outcome and results of a large prospective cohort are needed.